Modeling and Optimization of Bobbin Friction Stir Welding for AA6061-T6 alloy Utilizing Response Surface Methodology (Journal of University of Babylon for Engineering Sciences, 2018)
Bobbin friction stir welding (BFSW) is special kind of friction stir welding. This investigation aims to develop empirical models through mathematical relationships between the welding process parameters and mechanical properties of Aluminum alloy AA6061-T6 welded joint created by using bobbin tool and to find the optimum welding parameters. The welding speed range (40-200 mm/min) and rotational speed range (340-930 rpm) were utilized (as the used input factors) to find their effects on elongation, tensile strength and maximum bending force as the main responses.  These models were built using Design of Experiment (DOE) software ‘version 10’ with Response Surface Methodology (RSM) technique. The models adequacy were tested via the (ANOVA) analysis. The obtained models appeared that as the welding speed or rotational speed increases, the elongation, tensile strength and maximum bending force of the welded joint firstly rise to a maximum value and then drop. The optimum welding parameters were rotational speed (623.949 rpm) and welding speed (128.795 mm/min) with (6.33%), (204 MPa) and (6.216 KN) of elongation, tensile strength and maximum bending force, respectively. A proper harmonization was obtained between the models predicted results and the optimized ones with actual trial with 95% level of confidence.